True ghost stories - Deary, Terry (Scholastic, 1995)
Incredible? Impossible? Someone, somewhere has sworn that each of these nine terrifying tales is true... Strange, unexplained 'spirit stones' haunt a remote Australian farmstead. The horrifying apparition of a young girl avenges her own murder. A restless mummy walks abroad on Hallowe'en... Look at the facts and decide for yourself: do you believe in ghosts?